Ideals and practice in the study of Philippine Public Administration and Governance - Abueva, Jose Veloso (Philippine Journal of Public Administration, 2008)
This article attempts to explain the gap between the ideals and practice, visions, and reality in the study of Philippine Public Administration and Governance. It presents some defining characteristics thereof relating to the different phases and aspects of Philippine history and development. The article also tries to consolidate Philippine democracy after 22 years since the EDSA revolution in 1986 and discusses alternative responses to the mounting political and moral crises at present. The article ends with a vision the encapsulates ideas and ideals of the 1987 constitution.